Hydrogen Sulfide Donor GYY4137 Rescues NRF2 Activation in Respiratory Syncytial Virus Infection - Aline Haas de Mello; Tianshuang Liu; Roberto P. Garofalo; Antonella Casola (MDPI AG, 2022)
Respiratory syncytial virus (RSV) can cause severe respiratory illness in infants, immunocompromised, and older adults. Despite its burden, no vaccine or specific treatment is available. RSV infection is associated with increased reactive oxygen species (ROS) production, degradation of the transcription factor nuclear factor erythroid 2-related factor 2 (NRF2), and decreased antioxidant enzymes (AOEs), leading to oxidative damage and lung injury. Hydrogen sulfide (H2S) is an endogenous gaseous molecule that plays a physiological role in numerous cellular processes and a protective role in multiple pathological conditions, displaying vasoactive, cytoprotective, anti-inflammatory, and antioxidant activities. H2S can promote NRF2 activation through the sulfhydration of Kelch-like ECH-associated protein 1, the cytoplasmic repressor of NRF2. Here we investigated whether increasing cellular H2S levels could rescue NRF2 and NRF2-dependent gene expression in RSV-infected primary airway epithelial cells. We found that treatment with the H2S donor GYY4137 significantly increased NRF2 levels and AOEs gene expression by decreasing KEAP1 levels, and by modulating pathways involved in RSV-induced NRF2 degradation, such as NRF2 ubiquitination, and promyelocytic leukemia (PML) protein levels. These results suggest that the administration of exogenous H2S can positively impact the altered redox balance associated with RSV infection, which represents an important determinant of RSV-induced lung disease.